Influence of Cryopreserved Embryonic Brain Cells to Inflammation Mediators at Experimental Ishemic Insults - Goltsev, A. N.; Lebedinets, D. V.; Porozhan, Ye. A. (Problems of Cryobiology and Cryomedicine, 2008)
Contents of interferon-Ð³ (IFN-Ð³) and interleukin-10, pro- and anti-inflammatory cytokines in blood rats with an ischemic insults (II) and after treatment by intravenous injection of cryopreserved embryonic brain cells (CEBC) were studied. On the basis of the received data it is concluded, that for preventive maintenance and treatment of II it is necessary to carry out the therapeutic correction directed to modulation of inflammatory immune response of an organism at cytokine expression level.